A nationwide comparative analysis of the prevalance and determinants of non-communicable diseases risk factors between Jordanian and displaced Syrian populations - Nour Abdo; Sharifeh Almasaid; Ahlam J. Alhemedi; Ahmad Abdalmajeed Alghzawi; Albaraa Abu Ata; Izzaldin Albojuq (BMC Public Health)
Abstract Background Focusing on noncommunicable diseases in displaced Syrian populations and comparing it Jordanians can improve health outcomes, reduce suffering, and better integrate displaced individuals into broader public health strategies. Methods A secondary analysis was conducted to STEPs 2019 Survey done in Jordan, the total sample size was 5713 participants, where a multistage stratified clustered sampling was used for both Jordanian and Syrian aged between 18 and 69 years. The Chi-square test was used to compare character variables while T-test was used for continuous variables. A multivariate stepwise logistic regression model was used to identify the risk factors for hypertension (HTN), diabetes (DM), and hyperlipidemia (HLD). Significance was set to 0.05 and was adjusted for multiple comparisons. Results Jordanians exhibit high rates of smoking (35.4%), and high salt intake (30.2%), while Syrians have lower vegetable intake (8%), were more involved in vigorous work-related activity (18.7%), and using active transportation (75.2%). HTN (50.2%), DM (12.3%) and HLD (84.5%) prevalence was higher in Jordanians. However, the HTN prevalence in displaced Syrians (46.6%) in this analysis was much higher than most recent reported numbers in literature prior to the war and DM (7.2%) was lower. HTN, DM, HLD and metabolic syndrome exhibited strong associations with demographic and lifestyle factors, where older age groups were more predisposed (p < 0.00). Both college and school education had lower odds from metabolic syndrome, (odds ratio [OR] = 0.29, 95% CI = 0.17–0.48), and (OR = 0.53, 95% CI = 0.37–0.76) respectively in both populations. Lower education was also associated with higher odds of HTN, DM, and dyslipidemia in Jordanian population only. DM had lower odds in men (vs. women) only in the Syrian population (OR = 0.68, 95% CI = 0.51–0.92). Rural residence had higher odds of HTN in both populations (OR = 1.24, 95% CI = 1.02–1.49). The use of active transportation has lower odds of MS and DM in both populations. Being active in leisure-or-work was positively associated with lower odds of MS in both populations. Jordanians showed higher odds of MS (OR = 1.48, 95%CI 1.15–1.89) and HDL compared to Syrians (OR = 1.29, 95% CI = 1.09–1.52). Conclusion The disease burden in Syrian refugees in Jordan is related to barriers to healthcare access and economic stability, lower awareness when to seek medical attention, and increasing stress levels, which all leads to disruption in the longitudinal care needed for NCD management. This necessitates tailored interventions to ensure accessibility and responsiveness to healthcare needs as the blame is not on displacement by itself given its effect cannot be proven.